Between Religious Marketplace and Spiritual Wasteland: Religion in the British Atlantic World - Pestana, Carla Gardina (History compass, 2004)
The predominant metaphors in use for describing religion in the British Atlantic world are marketplace and wasteland - the first presenting religion as a product to be sold and consumed, the second asserting that religion was not successfully planted in colonies (at least not outside of New England). Both of these constructs for understanding religion's nature and role rely heavily on the perspective of clergymen. Although they left us much that was written on religious belief and practice for the period to 1800, clergy have a particular perspective and the sources they penned skew the presentation of religion toward competition and absence. These two ways of looking at faith are in fact two sides of the same clerical coin, and ought to be accepted only with caution, if at all. This article argues that we must read these denunciations with a critical eye and look beyond them to appreciate the vibrancy of lay religious faith and practice even in those very places that the clergy vociferously criticized.